Inquiry Method Innovation of Descriptive Text Material In Speaking Course At STKIP AL Maksum - Fernandi De Napoli Marpaung; Alvira Shahira; Ratna Padang (The Seall Journal, 2023)
Innovation is very important in the learning aspect, especially in learning English. Choosing the right learning model for a material has a significant effect on the desired learning outcomes. This study aims to provide innovation in inquiry teaching methods on descriptive text learning materials. A quantitative approach with a pre-experimental design was used in this study. In this study, there were 25 students who participated. All of these students followed the entire learning process that was carried out. The instrument used to measure conceptual mastery was in the form of a practical test instrument using an assessment rubric, while a questionnaire was used to measure student responses. The result shows 84% of students said that the activities carried out in the learning process were new to them and 56% has a little difficulty; it means that there has been a process of students' critical thinking about the learning given, according to the expected inquiry method, 68% of students thought that the learning activities carried out made students interested in learning the concept of descriptive text, the innovations that were carried out actually received a good response, as many as 72% felt that the method had become more enjoyable. The learning activities made it easier for students mastering the concept of descriptive text" obtained 80% results found it easier to understand the basic concepts of material about descriptive texts, and 84% did not feel bored in learning activities. Thus, teachers must continuously develop innovative learning methods and media in order to make the learning process more successful and interesting for students. Keywords: Innovation, Inquiry, descriptive text